The messenger matters: environmental nonprofit organisations' public faces, information recipients' worldviews, and the credibility of ENPOs' disclosed policy information. (15th March 2022) - Liu, Li-Yin; Morris, Rikki
Abstract: Environmental nonprofit organisations (ENPOs) have become crucial policy actors who have undertaken information campaigns to attract public attention and to gain public support for policies. However, the credibility of policy information released by ENPOs is understudied. To fill the gap, this study utilised Douglas and Wildavsky's cultural theory (CT), to seek answers to two questions: 1) how do ENPOs' public faces affect public perception of the credibility of the policy information released by their organisations? 2) how do the public's worldviews affect trust in information released by ENPOs with different types of public faces? The evidence from an online survey confirms what CT predicted: Hierarchs tend to believe information released by policy actors with proper authority; individualists tend to believe information released by policy actors who favour economic growth over environmental protection; egalitarians favour all pro-environmental policy information even if the information is released by noncredible policy actors.